PENGARUH SERTIFIKASI TERHADAP PROFESIONALISME, KINERJA, DAN KESEJAHTERAAN GURU PADA MTsN DI SAMPIT KEMENTERIAN AGAMA KABUPATEN KOTAWARINGIN TIMUR - Nurhasanah, Nurhasanah (Jurnal Aplikasi Manajemen Pendidikan, 2015)
Teacher education is a subject that has a position to determine the success of education itself. With the teacher certification program is expected to increase professionalism, performance and welfare of teachers. This study was conducted in MTsN Sampit East Kotawaringin, with the title "Effect of Certification on Professionalism, Performance and Welfare of Teachers at the Ministry of Religious MTsN Sampit East Kotawaringin ". The goals to be achieved in this research are: Determine the influence of certification on the professionalism of teachers, Determine the influence of certification on teacher performance, Knowing the professionalism influences affect the performance, Knowing the effect on the welfare of the teacher certification, and Knowing how influence on the welfare of teachers' performance in MTsN Sampit East Kotawaringin.The data analysis technique used is the analysis of SEM-PLS (Structure Equation Modelling- Partial Least Square) are grouped into two, namely statistical analysis descriptive and inferential statistical analysis. PLS analysis results yield coefficient lines as follows: X= 0.644 and t-value= 9.938 + Y1 = 0.155 and t-value= 1,110+ Y2= 0.407 and t-value= 3.138 + Y3= 0.036 and t-value= 0.184 + Y4= 0.522 and t-valui,= 5.148. The conclusion of this study are: Teacher Certification significant effect on Teacher Professionalism, Teacher Certification no significant impact on teacher performance, Teacher Professionalism significant impact on teacher performance, Teacher Certification does not significantly influence the Teachers' Welfare, Teacher Performance significantly influence the Teachers' Welfare at in MTsN Sampit East Kotawaringin.The suggestion (1) For the Head Office of the Ministry of Religious East Kotawaringin in order to improve the quality of teachers by organizing training and professional academic as well as provide oversight and assessment of teachers especially those who have certification in order to become a teacher profesiona. (2) For teachers to create professional development work in order to obtain academic achievement and become a professional.